Realization of large capacity ATM switches. - Kou, K.Y.
Large-capacity ATM switches, with switching capacity in excess of 40 Gb/s or 100 Gb/s, are becoming an essential part of network growth. To realize such switches requires technology know-how as well as implementation trade-off considerations. This article provides a system-level exploration of large-capacity ATM switches in terms of switch fabric scalability, cell buffer management, buffer design trade-off, call processing capabilities, and future trends in switch design
Keywords: VLSI; Buffer design trade-off.; Call processing; Cell buffer management; Cost-effective nonblocking switching system; Large capacity ATM switches; Low cell loss; Low cross-switch delay; Policing functions; Switch design; Switch fabric scalability; System-level considerations; User interface